2017
DOI: 10.1186/s12887-016-0759-7
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium adolescentis protects against necrotizing enterocolitis and upregulates TOLLIP and SIGIRR in premature neonatal rats

Abstract: BackgroundNecrotizing enterocolitis (NEC) is a serious gastrointestinal disorder that is often seen in premature infants. Probiotics decrease the risk of NEC; however, the mechanism by which probiotics work is not clear. The goal of this study was to evaluate the preventive effect of Bifidobacterium adolescentis in an NEC rat model.MethodsSprague-Dawley neonatal rats were obtained by caesarean section after 20-21 d gestation and randomly divided into the following 3 groups: dam fed (DF), formula fed (FF), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
98
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(123 citation statements)
references
References 42 publications
18
98
5
1
Order By: Relevance
“…Supplementation with glycine increased mRNA expression of ileal ERBB2IP. Previous studies showed that Tollip bound to IL-1 receptor-associated kinase (IRAK) and inhibited IRAK phosphorylation to downregulate TLR4 signaling [ 54 ]. This indicates that supplementation with glycine could suppress the activity of IRAK by increasing the mRNA expression of Tollip, resulting in impairing the signaling from TLR4 to downstream pathways, and reducing the synthesis of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation with glycine increased mRNA expression of ileal ERBB2IP. Previous studies showed that Tollip bound to IL-1 receptor-associated kinase (IRAK) and inhibited IRAK phosphorylation to downregulate TLR4 signaling [ 54 ]. This indicates that supplementation with glycine could suppress the activity of IRAK by increasing the mRNA expression of Tollip, resulting in impairing the signaling from TLR4 to downstream pathways, and reducing the synthesis of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent excessive inflammatory responses, many mechanisms can negatively control inflammatory signaling pathways. So far, several negative regulators of TLR4 (such as SOCS1 and Tollip) and NOD (such as ERBB2IP and ACAP1) signaling pathways have been identified and characterized 44 – 46 . Our data reflected that the LPS-challenged pigs had reduced mRNA expressions of ileal ERBB2IP and Tollip, which is in agreement with the study of Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al . demonstrated that Tollip down-regulated the TLR4 signaling pathway via bounding to IL-1 receptor-associated kinase (IRAK) and inhibiting IRAK phosphorylation 44 . This indicates that supplementation with Glu could inhibit the activity of IRAK through increasing the gene expression of Tollip, leading to impair the signaling from TLR4 to downstream pathways and reduce the synthesis of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important pathways that mediates the balance between injury and repair in the premature intestine, and that plays a key role in NEC pathogenesis, is the Toll-like receptor (TLR) family of bacterial recognition receptors, specifically Toll-like receptor 4 (TLR4), which recognizes lipopolysaccharide (LPS) on gram-negative bacteria. 17 Key evidence linking TLR4 with the pathogenesis of NEC include the findings that the expression of TLR4 in the intestinal epithelium is increased in mice and human beings with NEC, 18 , 19 activating mutations in TLR4 signaling pathways are seen in human NEC, 20 , 21 , 22 , 23 and novel TLR4 inhibitors prevent and treat NEC in animal models and attenuate proinflammatory signaling in human NEC tissue ex vivo, 24 whereas mice lacking TLR4 in the intestinal epithelium are protected from NEC development. 25 It is noteworthy that there are other pathways that also play a role in the pathogenesis of NEC, many of which are downstream of TLR4, and these have been reviewed extensively by us recently elsewhere, 15 while other investigators have shown that the premature intestine is more prone to inflammation 26 in part through the expression of innate immune response genes including TLR4 and its gene family members, 27 which is supportive of this concept.…”
Section: A Unifying Hypothesis For Nec Development: An Imbalance Betwmentioning
confidence: 99%